Modeling and Performance Analysis of a Series-Parallel AC Circuit under Supply Voltage Variations Using Simulation - Eka Feby Ronauli Lubis; Nurhafiz Ahmad Rangkuti; Nirwan Sinuhaji; Indah Mawati Giawa (Karya Techno Solusindo, 2026)
Series-parallel Alternating Current (AC) circuits are widely used in electrical power distribution and electronic systems because their operating characteristics are strongly influenced by supply voltage variations. Although simulation-based circuit analysis using Multisim has been widely applied in engineering education, studies systematically investigating the operating characteristics of series-parallel AC circuits over a broad range of supply voltages remain limited. This study aims to analyze the effect of gradual supply voltage variation on the operating characteristics of a series-parallel AC circuit using Multisim simulation. A quantitative experimental approach based on computer simulation was employed. The simulated circuit consisted of two resistors (220 Ω and 230 Ω) and two lamps connected as electrical loads. The supply voltage was gradually varied from 100 V to 320 V to observe changes in the operating conditions of the loads. The simulation showed that increasing the supply voltage progressively changed the lamp operating conditions, ranging from no illumination at 100 V, low brightness at 130 V, gradual increases in brightness at intermediate voltage levels, maximum brightness at 300 V, and lamp failure at 320 V due to excessive applied voltage. These observations are consistent with the theoretical relationships described by Ohm's Law, where increasing supply voltage results in greater electrical power delivered to resistive loads. The findings suggest that Multisim provides a practical environment for the preliminary evaluation of circuit behavior under different supply voltage conditions. However, the conclusions of this study are limited to simulation-based observations and require further validation through quantitative electrical measurements and hardware experiments. REFERENCES Anindya et al. (2025). Analisis Arus Dan Tegangan Pada Rangkaian Seri Dan Paralel Berdasarkan Hukum Ohm. Phydagogi : Jurnal Fisika Dan Pembelajarannya, 7(2), 1–8. Bhowmic, A. (2024). Verification of Electrical Circuit Simulation Results Using Multisim. Dewi Tiyas Saputri, Ayu Widiana Putri, & Aisyiyah Marfa Berliana Buanasari. (2025). Pengaruh Tegangan Terhadap Besar Kuat Arus Listrik Pada Pengukuran Hukum OHM Berbasis Simulasi Phet HTML5. Jurnal Teknik Mesin, Industri, Elektro Dan Informatika, 4(1), 321–331. https://doi.org/10.55606/jtmei.v4i1.4843 Dewy, M. S., & Isnaini, M. (2022). Pengembangan Modul Pembelajaran Berbasis Software Simulasi Ni Multisim Pada Mata Kuliah Rangkaian Listrik Dc. 9(1). Fan, C., Yang, M., Zhao, Y., Geng, X., & An, J. (2026). Research and Practice of a Virtual Simulation Circuit Experiment Platform based on LabVIEW and Multisim. In Academic Journal of Science and Technology (Vol. 19, Number 1). Halim, A., Alinda, M., Mahzum, E., & Wahyuni, A. (2024). Impact of Using PhET and NI Multisim Simulation on Understanding Electrical Circuit Concepts. https://doi.org/10.21009/1 Hilma, & Malik, A. (2024). Analisis Pengaruh Tegangan dan Hambatan Terhadap Kuat Arus dengan Menggunkan Phet Simulation. JFT: Jurnal Fisika Dan Terapannya, 10(2), 76–85. https://doi.org/10.24252/jft.v10i2.39275 Mabruroh, F., Talakua, P., Suhendi, H. Y., & Maipauw, M. M. (2025). The Utilization of Virtual Reality in Ohm’s Law Experiment Simulation. Jurnal Pendidikan Dan Ilmu Fisika, 5(1), 25–39. https://doi.org/10.52434/jpif.v5i1.42510 Malik, A., Asyidik, D., Nursamsika, K. H., Khotimah, R. N., & Fitriyani, R. (2020). Learning Ohm’s Law through Electric Puzzle Media. https://doi.org/10.21009/1 Nasab, M. R., Cometa, R., Bruno, S., Giannoccaro, G., & Scala, M. La. (2024). Power Systems Simulation and Analysis: A Review on Current Applications and Future Trends in DRTS of Grid-Connected Technologies. In IEEE Access (Vol. 12, pp. 121320–121345). Institute of Electrical and Electronics Engineers Inc. https://doi.org/10.1109/ACCESS.2024.3452468 Nuryanto. (2017). Analisa Rangkaian Elektronika Dengan Menggunakan Program Simulasi Spice. http://www.orcad.com/pspicead.aspx. Putri et al. (2025). Analisis Hubungan Tegangan dan Arus dalam Rangkaian Seri dan Paralel Berdasarkan Hukum Ohm. Jurnal Fisika Dan Pembelajarannya, 7(2), 201–206. Rangkuti, N. A. (2026). Analisis Topologi Rangkaian Seri-Paralel Berbasis Simulasi Multisim Untuk Evaluasi Distribusi Arus Dan Tegangan. Hadron Jurnal Fisikadan Terapan, 8, 1–6. Ridwan, R., & Kembuan, D. R. E. (2021). Efektivitas Penggunaan Simulasi dengan Multisim Berbantuan Virtual Laboratory untuk Meningkatkan Kemampuan Berpikir Kritis Mahasiswa Jurusan Pendidikan Teknik Elektro. Jurnal Kiprah, 9(1), 39–47. https://doi.org/10.31629/kiprah.v9i1.3235 Rupawanti, N. (2018). J E : Electronic Control, Telecomunication, Computer Information and Power Systems Studi Karakteristik Transformator Daya Listrik dengan Multisim 12.0. 3, 5–8. Saha, A. K. (2022). A Real-Time Simulation-Based Practical on Overcurrent Protection for Undergraduate Electrical Engineering Students. IEEE Access, 10, 52537–52550. https://doi.org/10.1109/ACCESS.2022.3175813 Sidiq & Sukandar. (2023). Analisis Perbandingan Karakteristik Arus Dan Tegangan Pada Rangkaian Listrik Seri Dan Paralel. 1–4. Surahmat, A., & Dedy Fu’ady, T. (2020). Simulasi Rangkaian Seven Segment Menggunakan Multisim Pada Pembelajaran Rangkaian Elektronika Analog Dan Digital Di Smks Informatika Sukma Mandiri. Sya’ban, A. N., Faiza, D., Thamrin, & Jasril, I. R. (2024). “METRIKA”: Electronics Trainer Media for Supporting Learning in the Application of Ohm’s Law and Kirchhoff’s Law. Journal of Hypermedia & Technology-Enhanced Learning, 2(1), 63–79. https://doi.org/10.58536/j-hytel.v2i1.112 Zhang, M., & Pan, S. (2023). Flipped Classroom of Electrical and Electronic Technology based on Multisim Simulation. In Academic Journal of Science and Technology (Vol. 5, Number 1).